Β-Hydroxyisovalerylshikonin inhibits IL-1β-induced chondrocyte inflammation via Nrf2 and retards osteoarthritis in mice. Issue 11 (10th November 2020) - Chen, Ximiao; Gu, Mingbao; Jin, Jie; Ren, Chenghao; Pan, Zongyou; Wu, Yaosen; Tian, Naifeng; Wu, Aimin; Sun, Liaojun; Gao, Weiyang; Wang, Xiangyang; Bei, Chaoyong; et al.
Abstract : β-HIVS blocks the activity of NF-κB by activating the Nrf2/HO-1 pathway, thereby inhibiting IL-1β-induced inflammation and ECM degradation. Abstract : Osteoarthritis is a chronic degenerative disease characterized by cartilage destruction. It is the fourth most disabling disease worldwide and is currently incurable. Inflammation and extracellular matrix (ECM) degradation are considered to be substantial reasons for accelerating the progression of OA. β-Hydroxyisoamylshikonin (β-HIVS) is a natural naphthoquinone compound with anti-inflammatory and antioxidant activity. However, the effect of β-HIVS on OA is still unclear. In this study, we found that β-HIVS can down-regulate the expression of NO, PEG2, IL-6, TNF-α, COX-2, and iNOS, suggesting its anti-inflammatory effects in chondrocytes; we also found that β-HIVS may down-regulate the expression of ADAMTS5 and MMP13 and up-regulate the expression of aggrecan and collagen II to inhibit the degradation of ECM. Mechanistically, β-HIVS inhibited the NFκB pathway by activating the Nrf2/HO-1 axis, thereby exerting its anti-inflammatory and inhibitory effects on ECM degradation. In vivo experiments also proved the therapeutic effects of β-HIVS on OA in mice, and Nrf2 is the target of β-HIVS. These findings indicate that β-HIVS may become a new drug for the treatment of OA.